Valeriu Soltan; Lectures on Convex Sets, World Scientific Publishing Co. Pte. Ltd., Singapore 2015, x+405 pp, ISBN 978-9814656689; ISBN 978-9814656696. - POPOVICI, Nicolae (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The present book is devoted to a systematic study of algebraic and topological properties of convex subsets of the Euclidean space Rn. As it is known these objects form the background of various mathematical disciplines, as convex geometry and operation research.